INCREASING SALES OF TUNA FISH SHREDDED PRODUCTS BY AMPENAN COASTAL WOMEN (IRT MELATI GROUP) DURING THE COVID 19 PANDEMIC - M. Yusuf, Siti Yulianah; Utami, Vidya Yanti; Rispawati, Dewi; Hermato, Basuki Sri; Rifaid, Rifaid (JCES (Journal of Character Education Society), 2021)
Abstrak: IRT Melatimerupakan kelompok yang didirikan oleh Perempuan Pesisir Ampenan untuk mengolah hasil lautmenjadi produk abon ikan. Setelah melakukan observasi singkat kelokasi usaha tersebut, Tim menemukan berbagai permasalahan mitra, khususnya dalam aspek pemasaran produk, aspek manajemen usaha dan aspek higienitas proses produksi. Melalui kegiatan pengabdian, diharapkandapat memberikan solusi bagi Mitra untuk menentukan strategi pemasaran yang tepat, guna menentukan media promosi dan memperluas wilayah pemasaran. Selain itu Mitra dapat membuat laporan keuangan untuk mencatat semua transaksi secara sistematis, serta Mitra dapat menerapkan protokol kesehatan dalam proses produksi, menjaga kebersihan dapur serta alat-alat produksi. Merode kegiatan ini diawali dengan memberikan penyuluhan, pelatihan serta pendampingan kepada Mitra terkait ketiga aspek permasalahan yang ditemukan. Hasil dari kegiatan ini adalah: a) Terdapat peningkatan penjualan produk abon ikan dan pengembangan usaha mitra; (b) Terdapat peningkatan keberdayaan anggota IRT dalam menggunakan media social sebagai alat untuk promosi dan memperluas pasar; (c) Mitra dapat membuat laporan keuangan sederhana secara sistematis; (d) Terdapatnya kesadaran Mitra dalam menerapkan protokol kesehatan pada proses produksi, menjaga kebersihandapursertaalat-alatproduksi.Abstract:Â  IRT Melati is a group founded by Ampenan Coastal Women to process marine products into shredded fish products. After conducting a brief observation at the location of the business, the Team found various problems with the partners, particularly in the aspects of product marketing, aspects of business management and hygiene aspects of the production process. Through community service activities, it is expected to provide solutions for Partners to determine the right marketing strategy, in order to determine promotional media and expand the marketing area. In addition, Partners can create financial reports to systematically record all transactions, and Partners can apply health protocols in the production process, maintain the cleanliness of kitchens and production tools. This method of activity begins with providing counseling, training and assistance to Partners regarding the three aspects of the problems found. The targets to be achieved from this activity are: a) There is an increase in the sale of shredded fish products and business development of partners; (b) There is an increase in the empowerment of IRT members in using social media as a tool for promotion and expanding the market; (c) Partners can produce simple financial reports in a systematic manner; (d) There is awareness of Partners in implementing health protocols in the production process, maintaining the cleanliness of kitchens and production tools.